Contributions of competition and climate on radial growth of Pinus massoniana in subtropics of China - Liang, Hanxue; Huang, Jian-Guo; Ma, Qianqian; Li, Jingye; Wang, Zhou; Guo, Xiali; Zhu, Huoxing; Jiang, Shaowei; Zhou, Peng; Yu, Biyun; Luo, Dawei (Agricultural and forest meteorology, 2019)
It is critical to investigate the effects of competition and climate on forest growth as they are main forces affecting forest dynamics. However, in subtropics of China such a study has never been conducted. Here we conducted a pioneer study to evaluate the effects of competition and climate on growth of Chinese red pine (Pinus massoniana) in mixed forests of subtropical China along a broad latitudinal gradient (23°N∼32°N). Twenty-three plots (20m × 20m) were randomly selected from 11 sites and competition and tree radial growth data were collected. Principal component analysis (PCA) was used to detect the potential spatial pattern in site-specific standard tree-ring chronologies during the common period (1990-2015). The linear mixed-effect models (LMMs) were employed to quantify the relationships between cumulated basal area increment (5, 10, 15, 20 and 25 years) of subject trees and six distance-independent competition indices. The relationships between tree radial growth and climate were evaluated by response analyses. Finally the best predicted competition index and climate factor were employed in a full model and their relative importance were calculated. The PCA results allowed classifying the mixed forests into southeastern and northern groups along the Nanling Mountains and Wuyi Mountains. LMMs results revealed that competition pressures mainly come from density and size of larger individuals. Response coefficients demonstrated that precipitation in September and sunshine duration in October influenced trees radial growth of southeastern group and northern group respectively. Our results clearly showed that effects of competition on tree radial growth decreased from southeast to north while effects of climates increasing over this large spatial scale. This is the first attempt to clarify the effects of competition, and further quantify the contributions of competition and climate on tree radial growth in China subtropics. Our finds will certainly contribute to a better policy-making for sustainable forest management.